Variable Properties of Auditory Scene Analysis in Music - Adam Rosiński (Arts)
This article explores the variable properties of auditory image analysis during the perception of musical works, which are influenced by the specific elements to which the listener directs their attention. Traditional analyses of musical compositions typically involve brief comparisons with auditory phenomena described in scientific studies, such as those by A.S. Bregman. However, these analyses are often limited, offering only a narrow perspective on the works. In contrast, the approach presented in this article extends the theories and experiments developed by Bregman and others, providing a more comprehensive understanding of entire compositions or selected sections rather than focusing solely on isolated passages. This broader framework enhances auditory image analysis and serves as a foundation for further research. The expanded analysis integrates within music theory, enabling a deeper exploration of musical structures, particularly in the context of perceiving multilayered music where multiple sound sources may share similar acoustic features. The author illustrates how acoustic and perceptual factors contribute to complex mental representations through graphic and musical examples. To substantiate the claims, classical works by composers such as F. Chopin, A. Guilmant, and J.S. Bach are analysed, further highlighting the variable properties of auditory image analysis.